ANALYZING PARALLEL PROGRAMS WITH PIN. - Bach, Moshe; Charney, Mark; Cohn, Robert; Demikhovsky, Elena; Devor, Tevi; Hazelwood, Kim; Jaleel, Aamer; Chi-Keung Luk; Lyons, Gail; Patil, Harish; Tal, Ady (Computer (00189162), 2010)
The article discusses the use of Pin to analyze parallel programs. It states that Pin, a software system, performs a runtime binary instrumentation to facilitate building of pintools for program analysis. The article discusses that pintools, consist of different routines such as instrumentation, analysis, and callbacks, are used to collect information and analyze memory and threading errors such as the Intel Parallel Inspector and to improve program performance such as the Intel Parallel Amplifier.